Subcritical Butane and Propane Extraction of Oil from Rice Bran - Hua-Min Liu; Fei-Yun Wang; Hao-Yang Li; Xue-De Wang; Guang-Yong Qin (BioResources, 2015)
Rice bran oil was extracted using hexane, as well as subcritical butane and propane. The quality of rice bran oils obtained using these three solvents was comparatively studied. The results showed that subcritical fluid extraction oil showed higher concentrations of health-conducive components (such as vitamin E, oryzanol, and phytosterol) compared with hexane-extracted oil. Extraction solvent had an important effect on the distribution of linoleic acid and oleic acid. The sterol compositions in rice bran oils were identified to be composed of ethyl iso-allocholate, campesterol, stigmasterol, sitosterols, and cyclolanosts. NMR data showed that butane-extracted oil had the highest triacylglycerols (TAGs) content and that subcritical propane-extracted oil had the highest wax content among the oils extracted with these three extraction solvents. The oils extracted by subcritical butane and propane showed higher oxidative stabilities. These results indicate that subcritical fluid extraction technology could be a useful method for producing high-quality rice bran oils and could become widely used in industrial applications.